Solvability conditions for the first order elliptic systems on the plane - Ospanov, Kordan Nauryzkhanovich (Eurasian Mathematical Journal, 2012)
Unique solvability conditions are obtained for an elliptic system of two first order real partial differential equations with unbounded coefficients.